Mesenchymal stem cells from perinatal tissues promote diabetic wound healing via PI3K/AKT activation - Jiawei Huang; Qingwen Deng; Lai Ling Tsang; Guozhu Chang; Jinghui Guo; Ye Chun Ruan; Chi Chiu Wang; Gang Li; Hon Fai Chan; Xiaohu Zhang; Xiaohua Jiang (Stem Cell Research & Therapy)
Abstract Background Diabetic foot ulcers (DFUs) represent a major complication of diabetes, often leading to poor healing outcomes with conventional treatments. Mesenchymal stem cell (MSC) therapies have emerged as a promising alternative, given their potential to modulate various pathways involved in wound healing. This study evaluates and compares the therapeutic potential of MSCs derived from perinatal tissues—human umbilical cord MSCs (hUCMSCs), human chorionic villi MSCs (hCVMSCs), and human decidua basalis MSCs (hDCMSCs)—in a diabetic wound healing model. Methods We performed in vitro and in vivo studies to compare the efficacy of hUCMSCs, hCVMSCs, and hDCMSCs. Mass spectrometry was used to analyze the secreted proteins of the MSCs. We incorporated the MSCs into a polyethylene glycol diacrylate (PEGDA) and sodium alginate (SA) hydrogel matrix with collagen I (Col-I) to evaluate their effects on wound healing. Results All three types of MSCs promoted wound healing, with hUCMSCs and hCVMSCs showing stronger effects compared to hDCMSCs. Both hUCMSCs and hCVMSCs demonstrated robust wound healing kinetics, with enhanced keratinocyte proliferation (KRT14+/Ki67+ cells), maturation (KRT10/KRT14 ratio), and angiogenesis. In vitro studies demonstrated that the MSC-derived secretome enhanced keratinocyte proliferation and migration, endothelial cell function and stem cell recruitment, indicating robust paracrine effects. Mass spectrometry revealed a conserved set of proteins including THBS1 (thrombospondin 1), SERPINE1 (serpin family E member 1), ANXA1 (annexin A1), LOX (lysyl oxidase), and ITGB1 (integrin beta-1) which are involved in extracellular matrix (ECM) organization and wound healing, with the PI3K/AKT signaling pathway playing a central role. The PEGDA/SA/Col-I hydrogel demonstrated a unique balance of mechanical and biological properties and an optimal environment for MSC viability and function. Application of either hUCMSC- or hCVMSC-laden hydrogels resulted in accelerated wound closure, improved re-epithelialization, increased collagen deposition, and enhanced vascularization in vivo. Conclusions MSCs From perinatal tissues particularly hUCMSCs and hCVMSCs significantly enhance diabetic wound healing through PI3K/AKT pathway activation while hDCMSCs exhibited weaker efficacy. The PEGDA/SA/Col-I hydrogel supports MSC viability and function offering a promising scaffold for DFU treatment. These findings underscore the potential of specific perinatal MSCs and optimized hydrogel formulations in advancing diabetic wound care.